Neutrophil elastase promotes neointimal hyperplasia by targeting toll‐like receptor 4 (TLR4)–NF‐κB signalling. (6th July 2021) - Yang, Mei; Chen, Qishan; Mei, Li; Wen, Guanmei; An, Weiwei; Zhou, Xinmiao; Niu, Kaiyuan; Liu, Chenxin; Ren, Meixia; Sun, Kun; Xiao, Qingzhong; Zhang, Li
Abstract : Background and Purpose: Neointimal hyperplasia (NIH) is the fundamental cause for vascular diseases and vascular smooth muscle cell (VSMC) dysregulation has been widely implicated in NIH. Neutrophil elastase is a potential therapeutic target for multiple diseases. We investigated the role of neutrophil elastase in VSMC functions and injury‐induced NIH and explored the therapeutic potential of targeting neutrophil elastase in NIH. Experimental Approach: VSMCs were used to analyse the effects of neutrophil elastase. Proteomic analysis was used to identify potential neutrophil elastase targets. Artery injury model and neutrophil elastase inhibitor GW311616A were used to investigate the role of neutrophil elastase in NIH. Key Results: TNF‐α up‐regulated neutrophil elastase in VSMCs through modulating GAPBα/Runx1/CEBPα/c‐Myb signalling. Up‐regulated neutrophil elastase promoted VSMC migration, proliferation and inflammation. Toll‐like receptor 4 (TLR4) was identified as a target protein for neutrophil elastase in VSMCs and the TLR4/MyD88/IRAK1/TRAF6/NF‐κB regulatory axis was shown to be the signalling pathway for neutrophil elastase in VSMC pathology. Importantly, TLR4 inhibition abolished neutrophil elastase‐mediated VSMC dysregulation. Injury‐induced NIH was significantly reduced in both neutrophil elastase‐deficient mice and mice treated with GW311616A. The formation of neutrophil extracellular traps was impaired in injured arteries from neutrophil elastase‐deficient mice. Finally, a similar role for neutrophil elastase in human VSMC pathology was confirmed and we observed higher expression levels of neutrophil elastase but lower expression levels of TLR4 in human atherosclerotic lesions. Conclusion and Implications: We provide new insight into the molecular mechanisms underlying NIH and identify neutrophil elastase as a potential therapeutic target for vascular disease.